Market-based policies for nuclear nonproliferation. Issue 3 (3rd July 2016) - Wood, Thomas; Seward, Amy; Otto, Robert
ABSTRACT: Access to weapon-useable fissile material—highly enriched uranium and separated plutonium—is the primary technical barrier to nuclear-weapon development. Nuclear-nonproliferation policy is largely concerned with the secure distribution and use of these materials and the technologies that produce them. To the extent that both materials and technologies are traded in markets, the problem may be viewed as one of influencing markets to give an acceptable set of allocative outcomes. While governments long ago rejected a laissez-faire approach to these markets, most current policy is based on prescribed or proscribed behavior rather than market incentives. "Market-based" nonproliferation policies would act through incentives in the markets for nuclear materials and technology rather than by prescribing outcomes or behavior. Possible polices of this sort include subsidized enrichment services, credits to impute value to spent nuclear fuel, and new markets for scarce nuclear materials. While market-based policies will not replace command-and-control policies entirely, they could lead to efficient regulation that suffices to guide the choices of most market participants, reserving special, more forceful measures for the few difficult cases.